Precision Oncology: A Global Perspective on Implementation and Policy Development - Denis Horgan; Marcel Tanner; Charu Aggarwal; David Thomas; Surbhi Grover; Lina Basel-Salmon; Rodrigo Dienstmann; Tira Jing Ying Tan; Woong-Yang Park; Hadi Mohamad Abu Rasheed; Lillian L. Siu; Brigette Ma; et al. (JCO Global Oncology)
Despite the acknowledged merits of precision oncology (PO) and its increasing global implementation, its full potential for advancing care and prevention remains unrealized. The benefits are currently accessible to only limited patient segments because of multifaceted barriers. Successful implementation hinges on various factors—scientific complexities not limited to technical, clinical, regulatory, economic, administrative, and health care policy–related challenges. From building infrastructure to the associated costs, including research and development, testing, processing, and trained personnel, a lack of alignment persists. Administrative alignment with regulatory and payor acceptance is crucial. Health care policy must adapt to the ongoing shift from a one-size-fits-all treatment to a personalized approach. Without official endorsement of long-term gains over short-term costs and the health establishment's readiness for innovation, PO prospects, even in prosperous economies, may stagnate. Lower-income countries face exacerbated challenges, intensifying barriers to adoption. Nevertheless, growing awareness and utilization, driven by recognized potential for patients and public health, along with successful examples and advocacy, are progressively influencing policy for a more inclusive and beneficial approach to PO adoption.